EFFICIENCY, EQUITY, AND EFFECTIVENESS OF MALARIA FUNDING IN UGANDA: MAKING THE CASE FOR REFORMING PUBLIC FINANCING FOR HEALTH - Vincent Okungu (Rojan GÜMÜŞ, 2019)
Decreasing external funding for malaria requires high burden countries such as Uganda to increase domestic public financing to control and eliminate malaria. The aim of this study was to examine how the Government of Uganda, in collaboration with development partners and private sources of funding, has directed public resources in the recent past to help address the malaria burden. Data search and collection included national, regional and global reports and global data-bases. Government reports including National Development Plans, national health accounts (NHAs), national demographic health surveys, and other reports such as the Uganda Medicines Price Monitor, were included in the review. The findings indicate that government funding for malaria is limited (10% of total budget for malaria programming). Households (67%) are the main source of funds which makes malaria control in Uganda unsustainable. Public allocations are also inefficient with only 30% of funds allocated for preventive services contrary to global and national malaria control priorities. Evidence of inequity in the implementation of malaria programming are closely linked to poverty and ownership of preventive materials such as ITNs. Poor regions also report high malaria case incidence. Unavailability of anti-malarials is reported in lower level facilities serving mainly the poor. Overall progress in improving key malaria indicators is poor. There is also no correlation between expenditure on malaria and availability of ITNs (R2=0.6631). In conclusion, public financing for primary services such as malaria require reforms to strengthen health sector performance in terms of sustainability, efficiency, effectiveness and equity.